Preparation method and application of PVA-coated high-drug-loading-capacity microspheres based on electrostatic and coordination effects

By constructing a bridged network structure, PVA-covered microspheres, combined with electrostatic adsorption and coordination, the problem of low drug loading of clay-based controlled release pesticides is solved, and efficient and sustainable controlled release effect of pesticides is achieved.

CN119699321AActive Publication Date: 2025-03-28HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411762555.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing clay-based controlled release pesticides have low drug loading and low utilization rate, making it difficult to meet the needs of agricultural production.

Method used

By combining electrostatic adsorption and coordination, a bridged network structure of "clay-metal ion-organic ligand-metal ion-clay" was constructed to prepare PVA-coated high-drug-load microspheres.

Benefits of technology

It significantly improves the drug loading and utilization rate of pesticides, achieves efficient controlled release of pesticides, and is in line with the sustainable development direction of modern agriculture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119699321A_ABST
    Figure CN119699321A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of PVA-coated high-drug-loading-capacity microspheres based on electrostatic and coordination effects, and belongs to the technical field of novel pesticide preparation. According to the method, three kinds of economical and high-yield electronegative natural clay including ATP (Attapulgite), HNTs (Halloysite) and Clay are taken as research templates, a proper amount of Ca < 2 + > is adsorbed by utilizing an electrostatic effect to be coordinated with hexadentate ligand ethylenediaminetetraacetic acid (EDTA < 2->), loading of targeted drug molecule abamectin (AVM) and self-assembly of the clay are completed at the same time through a one-step method, micro-nano aggregate is formed, and the targeted drug molecule abamectin (AVM) and the clay are loaded into the micro-nano aggregate at the same time. And finally, coating the surface of the microsphere with a polyvinyl alcohol layer to develop a novel carrier system (namely the drug-loaded microsphere). The system has the advantages of being high in stability and biocompatibility, low in cost and easy to operate. On the other hand, bridging of EDTA < 2-> and Ca < 2 + > is sensitive to low pH of the environment, and controllable release under specific requirements can be achieved. And a practical basis and a theoretical reference are provided for realizing accurate delivery and efficient supply of medicines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of novel pesticide preparation, and in particular to a preparation method and application of PVA-coated high-drug-loading microspheres based on electrostatic and coordination effects. Background Art

[0002] With the increase of global population and the growing demand for food, agricultural production is facing multiple pressures, and the importance of using traditional pesticides to control and manage crop diseases and pests is increasing day by day. However, traditional pesticides usually face problems such as short-term efficacy and easy loss. In actual situations, they often need to be applied repeatedly and in large quantities, which not only causes serious waste, but also has adverse effects on the environment and non-target organisms.

[0003] In order to solve the above problems, controlled-release pesticide technology based on nanocarriers has attracted much attention in recent years. Its purpose is to adjust the release rate and release time of pesticides to achieve more efficient and accurate pest control. By utilizing the strong adsorption of nanocarriers, pesticides are released slowly in the absence of stimulation, which can significantly enhance the duration of drug efficacy and reduce drug loss. Under specific external stimuli, drug molecules on the surface of the carrier can be desorbed through physical and chemical reactions, which is conducive to the on-demand supply of pesticides. Therefore, controlled-release pesticides not only provide long-term crop protection and reduce application costs, but also reduce drug loss and reduce environmental pollution risks.

[0004] Among many nanomaterials, natural clay has become a hot topic in the field of pesticide research due to its low cost, abundant sources, high stability and safety. Its high specific surface area and rich pore structure give it excellent adsorption capacity, which can fix pesticide molecules and achieve stable controlled release function. However, existing clay-based pesticides only use the surface adsorption of clay to fix target molecules, and the pesticide loading is low, which cannot meet the needs of agricultural production and further development of a resource-saving society. In addition to using hydrogen bonds and intermolecular forces on the carrier surface to adsorb drugs, constructing vesicles, capsules and other cavity dosage forms to directly "endocytize" drug molecules is one of the important ways to increase drug loading. Natural clay itself does not have a large cavity, and it is difficult to significantly increase the drug loading only by relying on surface engineering such as chemical modification. Therefore, it is urgent to construct a new clay-based high-drug loading carrier system through physical and chemical effects.

[0005] As key technologies in drug loading, material synthesis, etc., electrostatic adsorption and coordination have attracted much attention in the field of materials. Electrostatic interaction enables target molecules with different electrical properties to be firmly bound to the surface or inside of the carrier through mutual attraction of charges. Coordination generally increases the structural stability of the material through the specific binding of metal ions and organic ligands, and even gives it special chemical properties. How to reasonably apply these technologies to improve the drug loading and utilization rate of existing clay-based controlled-release pesticides has become an urgent problem to be solved. Summary of the invention

[0006] The technical problem to be solved by the present invention is how to solve the problems of low drug loading and low utilization rate of existing clay-based controlled-release pesticides.

[0007] The present invention solves the above technical problems through the following technical means:

[0008] The first aspect of the present invention provides a method for preparing PVA-coated drug-loaded microspheres, comprising the following steps:

[0009] (1) Preparation of self-loading aggregates: The nanoclay material is mixed with calcium chloride, stirred, dried, and then mixed with an aqueous solution of disodium ethylenediaminetetraacetate (EDTA-2Na), and then an ethanol solution of the pesticide is added, stirred, and dried to obtain clay aggregates loaded with the pesticide;

[0010] (2) Preparation of controlled-release preparations: The pesticide-loaded clay aggregates are dispersed in a polyvinyl alcohol (PVA) aqueous solution and stirred evenly to obtain PVA-coated drug-loaded microspheres.

[0011] Preferably, the mass ratio of the nano-clay material, calcium chloride and disodium ethylenediaminetetraacetate is (0.1-0.3):2:2, and more preferably 0.2:2:2.

[0012] Preferably, the usage ratio of the nanoclay material to the pesticide is (0.1-0.3) g: (5-15) mL, and more preferably 0.2 g: 8 mL.

[0013] Preferably, the concentration of the pesticide is 3-8 mg / mL, more preferably 5 mg / mL.

[0014] Preferably, the dosage ratio of the pesticide-loaded clay aggregate to polyvinyl alcohol is (0.1-0.5) g: (40-60) mL, and more preferably 0.2 g: 50 mL.

[0015] Preferably, the concentration of the polyvinyl alcohol is 0.5-3 mg / mL, more preferably 1 mg / mL.

[0016] Preferably, the nanoclay material is any one or more of attapulgite (ATP), halloysite (HNTs), and calyx (Caly).

[0017] Preferably, the pesticide is any one or more of avermectin (AVM), imidacloprid (IMI), methyltetrachloride (MCPA), and thiamethoxam (THI).

[0018] The second aspect of the present invention provides PVA-coated drug-loaded microspheres prepared by the above preparation method.

[0019] The third aspect of the present invention proposes the use of the above-mentioned PVA-coated drug-loaded microspheres as controlled-release pesticides in the field of sustainable green agriculture.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention combines the electrostatic adsorption of clay and metal ions, and the coordination of metal ions and organic matter, to construct a bridged network structure of "clay-metal ions-organic ligands-metal ions-clay" to achieve self-aggregation of nanoclay. The micro-nano aggregates have many large-aperture cavities, and there are also a large number of active sites on the inner and outer surfaces, so they have the effects of physical encapsulation and chemical adsorption of pesticide molecules. In addition, the bridged network structure is sensitive to weak acids, which is conducive to the construction of a pH-responsive controlled-release carrier system. Therefore, PVA-coated drug-loaded microspheres with high drug loading based on electrostatics and coordination have been developed to achieve high pesticide loading and improve pesticide utilization, which is in line with the direction of sustainable development of modern agriculture and provides a feasible path for the sustainable development of global agriculture.

[0022] 2. The present invention takes the insecticide avermectin (AVM) as an example as a targeted pesticide, and three natural nanoclays attapulgite (ATP), halloysite (HNTs), and clay (Caly) as carriers. 2+ Electrostatic adsorption, EDTA 2- With Ca 2+ The coordination of ions responds to weak acid to achieve weak acid controlled rupture of the outer PVA protective film, aiming to overcome the problem of low drug loading of existing clay-based controlled-release pesticides and difficulty in further improving drug utilization, and to prepare a pH-responsive intelligent pesticide carrier system. This system can significantly increase the pesticide loading, achieve a surge in drug release under pH control, and significantly improve the controlled release performance of AVM. At the same time, it is low-cost, simple to operate, and environmentally friendly, and has certain application value.

[0023] 3. The drug-loaded microspheres of the present invention have high stability and biocompatibility, low cost and simple operation. At the same time, the clay-based aggregates have large pores and many active groups on the inner and outer surfaces, so the carrier system has both physical inclusion and chemical adsorption effects and can accommodate more drug molecules. In addition, EDTA 2- With Ca 2+ The bridge is sensitive to low pH in the environment, which is conducive to the dissociation of the carrier system at low pH and the controlled release of drugs under specific needs. This method uses electrostatic and coordination effects to give the carrier system the characteristics of high drug loading and easy operation. It is also environmentally friendly and highly stable, providing a new method for constructing drug carriers, providing a practical basis and theoretical reference for achieving precise drug delivery and efficient supply. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a comparison chart of the loading amount of AVM by three clay materials (ATP, HNTs, Caly) in Examples 1-3 of the present invention;

[0025] Figure 2 This is a comparison chart of the response of different pH conditions to the release of AVM from the drug-loaded microspheres in Example 3 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0028] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0029] Embodiment 1:

[0030] A method for preparing PVA-coated drug-loaded microspheres comprises the following steps:

[0031] 1) Preparation of self-assembled aggregates: First, 0.2 g of nano-attapulgite (ATP) was mixed with 40 ml of aqueous solution containing 2 g of calcium chloride (CaCl2) to form a uniform suspension. The mixture was mechanically stirred at 400 rpm for 12 h and then vacuum dried. 2 + mixed with 32 ml aqueous solution containing 2 g EDTA-2Na. Subsequently, 8 ml of 5 mg / ml avermectin (AVM) ethanol solution was quickly added to the suspension, mechanical stirring was continued for 12 hours, and vacuum drying was performed again to finally obtain ATP@Ca 2 -EDTA-AVM aggregates.

[0032] 2) Preparation of controlled release preparation: ATP@Ca loaded with AVM 2 0.2 g sample of +-EDTA-AVM self-assembled aggregates was dispersed in 50 ml of 1 mg / ml PVA aqueous solution and mechanically stirred for 2 h to obtain PVA-coated drug-loaded microspheres.

[0033] Embodiment 2:

[0034] The difference between this embodiment and embodiment 1 is that nano-attapulgite (ATP) is replaced by "nano-halloysite (HNTs)" to obtain HNTs@Ca 2 +-EDTA-AVM aggregate, the rest is the same as Example 1.

[0035] Embodiment 3:

[0036] The difference between this embodiment and embodiment 1 is that nano-attapulgite (ATP) is replaced by "nano-white clay (Caly)" to obtain Caly@Ca 2 +-EDTA-AVM aggregate, the rest is the same as Example 1.

[0037] The drug loading capacity and controlled release performance of the PVA-coated drug-loaded microspheres prepared in Examples 1-3 were tested:

[0038] Drug loading test:

[0039] Prepare a series of standard solutions (e.g., 0, 10, 20, 30, 40, 50 mg / L) using pure pesticides of known concentrations. Measure the absorbance of these standard solutions at a wavelength of 245 nm using a UV spectrophotometer. Plot the concentration (x-axis) against the absorbance (y-axis) to obtain a standard curve. Then accurately weigh 5 mg of the three drug-loaded microspheres and place the samples in 50 mL of ethanol water (V 乙醇 :V 水 =3:1) solution, ultrasonicate for 20 minutes to release the pesticide into the solution. Centrifuge to ensure that there are no suspended particles in the solution, and use a UV spectrophotometer to measure the absorbance of the sample solution at a wavelength of 245nm. Using the standard curve equation, calculate the concentration of the pesticide in the solution based on the absorbance of the sample.

[0040] like Figure 1 As shown, the three different clay materials ATP, HNTs and Caly in Examples 1-3 showed high drug loading capacity, and their loading amounts of avermectin (AVM) reached 274 mg / g, 372 mg / g and 279 mg / g respectively (i.e., drug loading rates were 274%, 372% and 279%, respectively). This shows that these clay materials have excellent drug loading performance, can embed a large amount of active ingredients per unit weight, and improve the use efficiency and persistence of pesticides.

[0041] Controlled release performance test under pH control:

[0042] 5-10 mg of the drug-loaded microspheres prepared in Example 1-3 were placed in 20 mL of ethanol water (V 乙醇 :V 水=3:1) solution, and the kinetic release test was carried out at different pH (5.5, 7.0 and 8.5). 1 mL of the suspension was collected at a specific time, and 1 mL of ethanol aqueous solution was added to compensate for the volume loss. After centrifugation and dilution, the supernatant was detected by UV spectrophotometer to measure the absorbance and calculate the AVM release rate.

[0043] Take Example 3 as an example (such as Figure 2 Analyze as shown:

[0044] At pH = 7, Caly@Ca 2+ -EDTA-AVM release was only 25-30% at 24h, indicating that the external PVA-based protective film can effectively prevent the rapid release of AVM under normal conditions, which is beneficial to prolong the duration of AVM. 2+ -EDTA-AVM release was 40-45% at 24h. On the other hand, after applying weak acid at pH-5.5, the AVM release rate reached nearly 85-90% within 24h, which was much higher than that of Caly@Ca at pH=7 and pH=8.5. 2+ -EDTA-AVM nanoparticles. The above results show that weak acid as a stimulus can trigger Caly@Ca 2+ The rapid diffusion of AVM in EDTA-AVM nanoparticles has great application prospects in sustainable green agriculture. The controlled release performance of Example 1 and Example 2 is similar to that of Example 3.

[0045] The results showed that at different pH values ​​(5.5, 7.0 and 8.5), the cumulative release rate of AVM within 24 hours was 85-90%, 25-30% and 40-45%, respectively. Compared with neutral and alkaline conditions, the release amount under acidic conditions increased significantly. The reason for this is that under weak acid conditions, H + The concentration increases. + It has strong coordination ability and can bind to the carboxyl group in the EDTA molecule. + With Ca 2+ Competition occurs between + Will gradually replace Ca 2+ The substitution weakens the binding site of Ca 2+ Coordination bond with EDTA.

[0046] Comparative Example 1:

[0047] [Jiangtao Dong, Wang Chen, Dunzhong Qin, Yuxia Chen, Jun Li, Chen Wang, Yeqing Yu, Jianguo Feng, Xuezhong Du. Cyclodextrin polymer-valved MoS2-embeddedmesoporous silica nanopesticides toward hierarchical targets via multidimensional stimuli of biological and natural environments, Journal of Hazardous Materials, Volume 419, 2021, 126404, ISSN 0304-3894] proposed to construct a cyclodextrin polymer (CDP)-valve molybdenum disulfide (MoS2)-embedded porous silicon (MSN) nanopesticide by simulating multidimensional stimulation of biological and natural environments. Among them, MoS2@MSNs nanoparticles (having a core-shell structure) are used as nanocarriers for pesticides. Its drug loading is only 23 mg / g, which is much lower than the drug loading of 274-372 mg / g of the materials in Examples 1-3 of the present invention.

[0048] Comparative Example 2:

[0049]

Zhongxuan Hu, Changlong Shu, Meijing Wang, Tingze Yang, Hongling Pei, Teng Wang, Siyu Sun, Fang Zhang. Eco-friendly pH-responsive iron-doped insectlarval frass extract as a hexaconazole nano-delivery system for controlling fungal disease and promoting crop growth, Chemical Engineering Journal, Volume 494, 2024, 153025, ISSN 1385-8947

[0050] Comparative Example 3:

[0051] [Zhiyuan Zhou, Gaohua Hu, Gang Tang, Yulu Liu, Xiaohong Zhang, Yuqi Huang, Guangxiao Yan, Jianhua Xiao, Weiyao Yan, Yongsong Cao, Fabrication of dual responsive microcapsules based on starch with enhanced foliar adhesion and photostability for improving control efficacy and reducing environmental risks, Chemical Engineering Journal, Volume 494, 2024, 153290, ISSN 1385-8947] pH and enzyme responsive pesticide microcapsules (AVE@CPS-Fe-TA) were constructed by encapsulating carboxylated porous starch (CPS) loaded with avermectin (AVE) in tannic acid-iron complex (Fe-TA). The loading rate of AVE@PS increased with the hydrolysis time of starch within 1-4 hours. When the hydrolysis time reached 5h, the loading rate of AVE@PS began to decrease with the extension of hydrolysis time. Therefore, the optimal condition for starch enzymatic hydrolysis is 4h, and the maximum drug loading is only 8%-10%. This is far lower than the drug loading of 274-372% in Examples 1-3 of the present invention.

[0052] Example 4: (The difference between this example and Example 1 is that the process parameters are slightly different)

[0053] A method for preparing PVA-coated drug-loaded microspheres comprises the following steps:

[0054] 1) Preparation of self-assembled aggregates: First, 0.1 g of nano-attapulgite (ATP) was mixed with 40 ml of aqueous solution containing 2 g of calcium chloride (CaCl2) to form a uniform suspension. The mixture was mechanically stirred at 400 rpm for 12 h and then vacuum dried. 2+ mixed with 32 ml aqueous solution containing 2 g EDTA-2Na. Subsequently, 5 ml of 8 mg / ml imidacloprid (IMI) ethanol solution was quickly added to the suspension, mechanical stirring was continued for 12 hours, and vacuum drying was performed again to finally obtain ATP@Ca 2 -EDTA-IMI aggregates.

[0055] 2) Preparation of controlled release preparation: ATP@Ca loaded with IMI 2 0.5 g sample of +-EDTA-IMI self-assembled aggregates was dispersed in 60 ml of 0.5 mg / ml PVA aqueous solution and mechanically stirred for 2 h to obtain PVA-coated drug-loaded microspheres.

[0056] Example 5: (The difference between this example and Example 1 is that the process parameters are slightly different)

[0057] A method for preparing PVA-coated drug-loaded microspheres comprises the following steps:

[0058] 3) Preparation of self-assembled aggregates: First, 0.3 g of nano-attapulgite (ATP) was mixed with 40 ml of aqueous solution containing 2 g of calcium chloride (CaCl2) to form a uniform suspension. The mixture was mechanically stirred at 400 rpm for 12 h and then vacuum dried. 2 + mixed with 32 ml aqueous solution containing 2 g EDTA-2Na. Subsequently, 15 ml 3 mg / ml thiamethoxam (THI) ethanol solution was quickly added to the suspension, mechanical stirring was continued for 12 hours, and vacuum drying was performed again to finally obtain ATP@Ca 2 -EDTA-THI aggregates.

[0059] 4) Preparation of controlled release preparation: ATP@Ca loaded with THI 2 0.1 g sample of +-EDTA-THI self-assembled aggregates was dispersed in 40 ml of 3 mg / ml PVA aqueous solution and mechanically stirred for 2 h to obtain PVA-coated drug-loaded microspheres.

[0060] The performance of the drug-loaded microspheres prepared in Examples 4 and 5 is similar to that in Example 1.

[0061] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing PVA-coated drug-loaded microspheres, characterized in that: The following steps are involved: (1) Preparation of self-loading aggregates: nano-clay material is mixed with calcium chloride, stirred, dried, mixed with an aqueous solution of disodium ethylenediaminetetraacetate, and then an ethanol solution of pesticide is added, stirred, and dried to obtain clay aggregates loaded with pesticides; (2) Preparation of controlled-release preparations: The pesticide-loaded clay aggregates are dispersed in a polyvinyl alcohol aqueous solution and stirred evenly to obtain PVA-coated drug-loaded microspheres.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the nano-clay material, calcium chloride and disodium ethylenediaminetetraacetate is (0.1-0.3):2:

2.

3. The preparation method according to claim 1, characterized in that: The dosage ratio of the nano-clay material to the pesticide is (0.1-0.3) g: (5-15) mL.

4. The preparation method according to claim 1, characterized in that: The concentration of the pesticide is 3-8 mg / mL.

5. The preparation method according to claim 1, characterized in that: The dosage ratio of the pesticide-loaded clay aggregate to polyvinyl alcohol is (0.1-0.5) g: (40-60) mL.

6. The preparation method according to claim 1, characterized in that: The concentration of the polyvinyl alcohol is 0.5-3 mg / mL.

7. The preparation method according to claim 1, characterized in that: The nano clay material is any one or more of attapulgite, halloysite and clay.

8. The preparation method according to claim 1, characterized in that: The pesticide is any one or more of avermectin (AVM), imidacloprid (IMI), methyltetrachloride (MCPA), and thiamethoxam (THI).

9. PVA-coated drug-loaded microspheres prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the PVA-coated drug-loaded microspheres according to claim 9 as controlled-release pesticides in the field of sustainable green agriculture.

Citation Information

Patent Citations

  • Pesticide carrier added with attapulgite and preparation method thereof

    CN106993611A

  • Preparation method of nano drug-loading system of leaf surface affiliated pesticide

    CN107853299A

  • Pesticide adsorption degradable composite film based on metal framework material and preparation method thereof

    CN111363180A

  • Polyvinyl alcohol-based pesticide slow-release film and preparation method thereof

    CN111823678A

  • PH response type pesticide slow-release hydrogel ball and preparation method thereof

    CN116114691A